2018
DOI: 10.1634/theoncologist.2017-0396
|View full text |Cite
|
Sign up to set email alerts
|

Ki67 Changes Identify Worse Outcomes in Residual Breast Cancer Tumors After Neoadjuvant Chemotherapy

Abstract: This study evaluates the change in Ki67 percentage before and after neoadjuvant chemotherapy (NAC) and its relationship with survival outcomes in patients with breast cancer who did not achieve complete pathological response (pCR). These patients, a heterogeneous group with diverse prognoses that cannot be treated using a single algorithm, pose a challenge to clinicians. This study identified a subgroup of these patients with a poor prognosis, those with luminal B-like tumors without a Ki67 decrease after NAC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 49 publications
8
52
1
4
Order By: Relevance
“…In the present study, we observed that the Ki67 level was obviously decreased after NAC, which was consistent with several published studies 29,31,33,34 . Moreover, the Ki67 level was significantly decreased in the no relapse or metastasis group compared to that in the relapse or metastasis group.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, we observed that the Ki67 level was obviously decreased after NAC, which was consistent with several published studies 29,31,33,34 . Moreover, the Ki67 level was significantly decreased in the no relapse or metastasis group compared to that in the relapse or metastasis group.…”
Section: Discussionsupporting
confidence: 94%
“…19 More important, several studies to date have demonstrated that changes in the Ki-67 labeling index from before to after NCT could provide prognostic value for patients with breast cancer. [24][25][26] Consistent with several previous studies, the results of the current study demonstrated that Ki-67 suppression was higher in the patients receiving NCET, which further confirms the clinical benefit of preoperative concurrent chemotherapy and estrogen deprivation. 22,27 It is interesting to note that subgroup analysis demonstrated that NCET might be more effective for patients with "luminal B-like" disease and higher Ki-67 levels.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the pCR rate, the difference between the pretreatment and posttreatment Ki‐67 labeling indices has been demonstrated to be a more accurate predictor of treatment benefit and long‐term outcomes for patients with ER‐positive breast cancer . More important, several studies to date have demonstrated that changes in the Ki‐67 labeling index from before to after NCT could provide prognostic value for patients with breast cancer . Consistent with several previous studies, the results of the current study demonstrated that Ki‐67 suppression was higher in the patients receiving NCET, which further confirms the clinical benefit of preoperative concurrent chemotherapy and estrogen deprivation …”
Section: Discussionsupporting
confidence: 89%
“…In patients with SBBC, 16 received NAC treatment, and only 10 patients survived during the follow-up time. Because changes in the characteristics of the tumor after NAC predict a different prognosis in patients with UBC [10][11][12][13], characteristics through core needle biopsy and surgical tissue section were collected (Supplementary table 5 and 6). The changes in characteristics were compared before and after NAC between the survival group and non-survival group (Table 6) and also recorded the response to NAC (Table 7).…”
Section: Changes Of Characteristics After Nac In Sbbcmentioning
confidence: 99%
“…Neoadjuvant chemotherapy (NAC) is a well-established approach to treat large or locally advanced breast cancer [5][6][7] and could be used to evaluate the tumor response to chemotherapeutic agents at the same time [8,9]. The consensus is that different responses in tumor size, biomarkers, or tumor type after NAC can affect prognosis in UBC [10][11][12][13]. Controversially, Mattea Reinisch et al reported that patients with BBC had a lower pathologic complete response (PCR) rate and a lower disease-free survival (DFS) than those with UBC [14].…”
Section: Introductionmentioning
confidence: 99%